The Role Of The Government In The Impact Of Hospital Hazardous Toxic Waste Pollution In Ponorogo - KARIZ, Sela Angelita; PRASETYO, Yogi (Indonesia Strategic Sustainability, 2025)
In Indonesia, the COVID-19 pandemic is closely linked to the rise in infectious waste produced by the general public and medical professionals. Assuming that many individuals are tainted Coronavirus, the medical clinics limit can influence and how much irresistible waste produced is increment. Irresistible waste remembers for the Hazardous Toxic Waste (B3) squander classification, which contains unsafe and harmful materials that can contaminate, harm, and jeopardize the climate, wellbeing, and the endurance of living things. Ponorogo Regency, which is known as a